What Does Jean-Jacques Rousseau and Chester I. Barnard Have to Do With Quiet Quitting? (American Journal of Management, 2023)
Media sources have blended aspects of social loafing with aspects of the free rider problem which they now call “quiet quitting.” Social loafing is decades old theory from the social psychology literature, used to explain why individuals work less hard in groups. The free rider problem is a theory, mainly from economics, that explains the insatiable desire of people who do not contribute to the cost of production for goods and services which they consume. Employees’ perceptions of a firm’s social contract inform their understanding of psychological contracts, and inevitably their interpretation of fairness in job descriptions. Managers who understand Jean-Jacques Rousseau’s “Social Contract” and Chester I. Barnard’s “Theory of Authority” will be better able to anticipate and mitigate against the collective will of employees. In this article, we present three recommendations that, if implemented correctly, will help managers resolve problems leading to quiet quitting.
Keywords: management; authority; Chester I. Barnard; contract; free rider; power; quitting; Rousseau; social loafing